Politics and fiscal policy under Lemass: a theoretical appraisal - Barry, Frank (Economic & Social Studies, 2009)
Lemass rejected Whitaker?s recommendations that direct taxes be reduced and public investment shifted from social to productive areas. This was arguably done for political reasons and because Lemass believed that it might be possible to establish a social partnership deal of the type that Eichengreen has argued to have played a crucial role in post-war European convergence on US living standards. Such a bargain could not be reached under Ireland?s industrial-relations system, however. The present paper contrasts the two systems and shows the adverse employment, investment and growth effects that such attempts would have had in Ireland.
Keywords: Lemass; Fiscal policy; Ireland; Economic development